1962
DOI: 10.1083/jcb.12.2.263
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Localization of Enzymes in Spleen

Abstract: Some properties of rat spleen ribonuclease have been studied, and the intracellular distribution of the enzyme and ribonucleic acid have been presented. Spleen ribonuclease exhibits maximal activity at pH 5.8, and although there is some evidence for the presence of an enzyme with an optimum at pH 7.0, it is not conclusive. The enzyme is concentrated primarily in the mitochondrial fraction, but significant quantities occur in the supernatant fluid. The latter contains ribonuclease inhibitor similar to that foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1962
1962
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…We have also found that there is a need for optimization based on cell type and tissue of origin. Specifically, high constitutive RNase activity in tissues such as the spleen (Eichel and Roth, 1962), pancreas (Dickman et al , 1960), and lungs (Aho et al , 1983) makes isolation of intact mRNA a challenge. Likewise, we discovered that the elevated levels of B cell RNase activity can be mitigated by simply increasing the concentration of RNase inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…We have also found that there is a need for optimization based on cell type and tissue of origin. Specifically, high constitutive RNase activity in tissues such as the spleen (Eichel and Roth, 1962), pancreas (Dickman et al , 1960), and lungs (Aho et al , 1983) makes isolation of intact mRNA a challenge. Likewise, we discovered that the elevated levels of B cell RNase activity can be mitigated by simply increasing the concentration of RNase inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of acid ribonuclease has been investigated in rat liver (10,12,22,96,99,100,318,331,397), including regenerating and precancerous liver (lo), in mouse liver f363), rat kidney (400,401), rat spleen (26,124,334), moure, rabbit, and chicken skeletal muscle (454a), rat brain (23), pig anterior pituitary (229), calf thymus (53), rat mammary gland (156), rat adipose tissue (123), chick embryo Mullerian ducts (42), rabbit leucocytes (76), rat azodye hepatoma, and Novikoff hepatoma (10).…”
Section: Ribonucleasementioning
confidence: 99%